Optimization Of Integrated Material Procurement Processes In The Vendor Managed Inventory (VMI) System - Mansur, Agus; Ramadhan, Fadhil Adita (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
This study aims to address challenges in the material procurement process within the steel fabrication industry, which currently relies on a manual, Excel-based system. Such a system is prone to data errors, delivery delays, and ineffective interdepartmental communication. The research employs a case study approach, incorporating direct observations, historical data analysis, and interviews with relevant stakeholders. The proposed solution is an integrated Vendor Managed Inventory (VMI) system, developed using the Waterfall model through stages ranging from requirements definition to system testing. Findings reveal that implementing the VMI system significantly enhances efficiency, transparency, and the speed of material procurement while improving collaboration between the company and its suppliers. Additionally, the system optimizes inventory management, reduces operational risks, and offers a scalable solution for various manufacturing sectors. In conclusion, the integrated VMI system contributes substantially to improving overall supply chain performance. Keywords: Efficiency, Integration, Inventory Management, Procurement, VMI System